STUDI LITERATUR: PENERAPAN MODEL ELLIS TERHADAP KEMAMPUAN PENCARIAN INFORMASI MAHASISWA - Fadhilah, Karishma Elok; Mariani Noor, Nina (Nazharat: Jurnal Kebudayaan, 2025)
Information search skills are one of the skills that must be mastered by a student. Information seeking ability is the ability possessed by individuals in utilizing digital media and other search tools effectively. This research was conducted with the aim of analyzing the application of the Ellis model in understanding students' information search behavior based on articles or studies that have been conducted. The Ellis model information search method is one of various types of information search methods. The literature study method was chosen by the researcher in reviewing and examining the literature in the form of scientific articles relevant to the research topic, especially related to student information search with the David Ellis Model. A total of 23 scientific articles obtained from journal databases such as Google Scholar, Garuda, and Scopus with a publication period of the last 6 years were collected and analyzed how information search activities were carried out by students. The information search model according to Ellis has six stages, namely, starting, chaining, browsing, differentiating, monitoring, and extracting. The results showed that Ellis' model is one of the methods used by students to search for information related to lecture assignments using internet-based or online information media facilities. Information search activities have become part of student life.